Gel Mechanical Properties of Milk Whey Protein-Dextran Conjugates obtained by Maillard Reaction - Spotti, Maria Julia (2013)
The effect of Maillard reaction on the mechanical properties of whey protein isolate (WPI) heat-induced gels was evaluated. WPI and dextran (15-25 kDa) conjugates were obtained by controlled dry heating during storage at 60°C and 63% relative humidity for 2, 5 and 9 days. Changes in browning intensity and content of free amino groups were used to estimate the Maillard reaction. A decrease in free amino groups of WPI was observed when increasing polysaccharide concentration and reaction time. An increase in both a* and b* CIE Lab colour parameters indicated the development of a reddish-brown colour, typical of the Maillard reaction. Uniaxial compression and stress relaxation tests were performed to measure the mechanical properties of mixed and conjugate gels. Maillard reaction significantly modified the mechanical properties of WPI/DX gels, and even prevented fracture when conjugate gels were subjected to 80% deformation in uniaxial compression test.